2017
DOI: 10.1016/j.jneb.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factorial Validity and Reliability of a Food Behavior Checklist for Low-Income Filipinos

Abstract: Objective To examine factorial validity, test-retest reliability, and internal consistency of a Tagalog-language food behavior checklist (FBC) for a low-income Filipino population. Methods Participants (n = 160) completed the FBC on 2 occasions 3 weeks apart. Factor structure was examined using principal component analysis. For internal consistency, Cronbach α was calculated. For test-retest reliability, Spearman correlation or intraclass correlation coefficient (ICC) was calculated between scores at the 2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Since internal consistency is affected by the number of subitems (Streiner, 2003), this was expected given the small number of items these subscales contained. Similar results were found in a previous study evaluating the Spanish and Tagalog versions of the FBC (Banna et al, 2010;Suzuki et al, 2017), in which the correlation coefficient for the low number of items involved was also low. The low value indicated that items in the subscales may have reflected independent food behaviors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Since internal consistency is affected by the number of subitems (Streiner, 2003), this was expected given the small number of items these subscales contained. Similar results were found in a previous study evaluating the Spanish and Tagalog versions of the FBC (Banna et al, 2010;Suzuki et al, 2017), in which the correlation coefficient for the low number of items involved was also low. The low value indicated that items in the subscales may have reflected independent food behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…This tool, a brief questionnaire containing items on food security and overall diet quality, has a photo that helps its users to visually perceive the information it contains. Previous studies have demonstrated the validity and reliability of the Spanish (Banna et al, 2010) and Tagalog (Suzuki et al, 2017) versions of the FBC and found it to evaluate nutrition education on dietary intake. This simple tool may also be used in Japan to evaluate the impact of guideline-based nutrition education in pregnant and postpartum women; hence, we have developed the Japanese FBC in 2022, and evaluated face validity (Fujita et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies are needed to further examine the psychometric properties of the tool, and Filipinos in other parts of the United States should be included in this work. 15,16 Furthermore, while this tool is intended to be administered on paper, other methods of assessing diet should also be considered, including those that involve use of technology.…”
Section: Introductionmentioning
confidence: 99%
“…In reviewing the literature with regard to dietary assessment tools developed for Filipinos in the United States, only one Tagalog-language tool was found. 15,16 The tool, a food behavior checklist, was based on a previously validated English-language assessment developed for a limited-resource population. 17,18 Validity and reliability of the Tagalog version were evaluated in low-income Filipinos in Hawaii.…”
Section: Introductionmentioning
confidence: 99%